Guilt as the „Knot" of Morality - Wiśniewski, Ryszard (Filozofia Chrześcijańska, 2012)
The author analyzes the main problems in defining semantic, psychological and social dimensions of conscience. Starting with etymology and with the research of linguistic tradition he distinguishes causative fault and guilt. Internalisation of guilt is treated as the most important issue for morality. This issue essentially creates a major “knot” of morality, however, it points to the objectified, social sense of guilt. From the perspective of conscience guilt reveals and makes possible genuine morality and the chance to adapt human own guilt in view of their personal development and of preserving dignity. The perspectives of the conscience analysis distinguished in the article require a thorough examination and discussion.